2011
DOI: 10.1371/journal.pcbi.1002247
|View full text |Cite
|
Sign up to set email alerts
|

The What and Where of Adding Channel Noise to the Hodgkin-Huxley Equations

Abstract: Conductance-based equations for electrically active cells form one of the most widely studied mathematical frameworks in computational biology. This framework, as expressed through a set of differential equations by Hodgkin and Huxley, synthesizes the impact of ionic currents on a cell's voltage—and the highly nonlinear impact of that voltage back on the currents themselves—into the rapid push and pull of the action potential. Later studies confirmed that these cellular dynamics are orchestrated by individual … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
179
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(185 citation statements)
references
References 65 publications
(189 reference statements)
6
179
0
Order By: Relevance
“…Within our work the intrinsic noise is due to the stochastic gating of the ion channels, i.e. the so-called channel noise which is inherently coupled to the electrical properties of the axonal cell membrane [19][20][21]. Interestingly, it has been shown that intrinsic channel noise does not only lead to the generation of spontaneous action potentials [22], but as well affects the neuronal dynamics at different levels, namely: (i) it can boost the signal quality [14,15], (ii) enhance the signal transmission reliability [23], (iii) cause frequency-and phase-synchronization features [24][25][26][27][28] and (iv) may result in a frequency stabilization [29], to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Within our work the intrinsic noise is due to the stochastic gating of the ion channels, i.e. the so-called channel noise which is inherently coupled to the electrical properties of the axonal cell membrane [19][20][21]. Interestingly, it has been shown that intrinsic channel noise does not only lead to the generation of spontaneous action potentials [22], but as well affects the neuronal dynamics at different levels, namely: (i) it can boost the signal quality [14,15], (ii) enhance the signal transmission reliability [23], (iii) cause frequency-and phase-synchronization features [24][25][26][27][28] and (iv) may result in a frequency stabilization [29], to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, for the pre-Bötzinger neuron model, we used conductance noise [32,33], where the stochastic terms are added to the conductance terms in the voltage dynamics:…”
Section: Stochastic Dynamicsmentioning
confidence: 99%
“…This could be the position of a molecular motor on a filament track [4], the length of a microtubule undergoing catastrophes [5] or a bacterium displaying run and tumble [6]. Another example at the single-cell level concerns membrane voltage fluctuations in a neuron due to the stochastic opening and closing of ion channels [7][8][9][10][11][12][13][14][15][16]. The discrete states of the ion channels evolve according to a continuous-time Markov process with voltage-dependent transition rates, whereas the membrane voltage evolves according to a piecewise deterministic equation that depends on the current state of the ion channels.…”
Section: Introductionmentioning
confidence: 99%